Recognizing clique graphs of directed edge path graphs - Gutiérrez, Marisa (2003)
Directed edge path graphs are the intersection graphs of directed paths in a directed tree, viewed as sets of edges. They were studied by Monma and Wei (J. Comb. Theory B 41 (1986) 141-181) who also gave a polynomial time recognition algorithm. In this work, we show that the clique graphs of these graphs are exactly the two sections of the same kind of path families, and give a polynomial time recognition algorithm for them.